Ship Pipe Layout Based on Grid Normalized Astar Algorithm - LIN Yan, ZHANG Qiaoyu, LOU Jiandi (Shanghai Jiaotong Daxue xuebao)
In order to solve the existing problems of relying on manual experience to adjust the algorithm parameters, large difference of weight coefficient, and single result in ship pipe layout, a grid normalized Astar (GNAstar) is proposed. First, the mathematical models are established using bounding box and the grid method. Then, each path node is determined by the normalized weight values of different targets using the branch pipes splitting method, grid marking values, and the parent-child grid search strategy. The cost objective of traditional Astar only considering path length is extended to the comprehensive layout objective of pipes including length, bend consumption, and installation suitability. Finally, the GNAstar proposed is compared with the traditional Astar in a simulation case, and different pipe systems in ship engine room are taken as cases to further compare with the ant colony algorithm and particle swarm-Astar. The results show that the GNAstar proposed can obtain effective engineering solutions, and designers can obtain the corresponding layout result by setting the normalized weight coefficients of different targets.